Recurrent Catatonia due to Episodic Obsessive-Compulsive Disorder - Soumitra Das; Sakshi Prasad; Palak Atul Fichadia; Abhigan Babu Shrestha; Ozge C. Amuk Williams; Anil Bachu (Case Reports in Psychiatry)
Background. Catatonia is regarded as a diverse type of motor dysregulation syndrome that includes mutism, immobility, catalepsy, negativism, stereotypies, and echo phenomena. Catatonia is known to coexist with a wide range of physical and mental health conditions, including mood disorders, schizophrenia, autoimmune disorders, and metabolic abnormalities. Albeit, the association between obsessive-compulsive disorder (OCD) and catatonia is underreported, and mechanisms are not well elucidated. Study. In this study, we present a case of a 36-year-old woman who developed episodes of catatonia during the course of her obsessive-compulsive disorder (OCD). Success rates have been recorded with both benzodiazepines and electroconvulsive therapy (ECT). Gauging the severity of her symptoms and poor drug compliance, the patient was opted for and successfully treated with ECT. She was also educated about OCD through a series of therapy sessions and exposure and response prevention (ERP) principles. She was maintained on ERP and adjunctive clonazepam upon discharge. On subsequent follow-ups, the patient seemed to be doing well and was eager to begin her job again. Conclusion. Our study shows a possible link between OCD and catatonia. Additionally, robust studies are needed in order to determine the pathophysiology of catatonia and the mechanism of ECT so that more beneficial therapeutics can be developed. A combination of ECT and antidepressants with ERP therapy for recurrent catatonia with OCD could be effective as a therapeutic modality.